2014
DOI: 10.1111/manc.12059
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Two‐part Tariff Licensing Mechanisms

Abstract: This paper studies the optimal two‐part tariff licensing contract for an internal patentee in a differentiated Cournot duopoly. We find that the type of the royalty payment, whether ad valorem or per‐unit, that it is optimal for the patentee depends on the kind of goods produced in the industry, more precisely on whether they are substitutes or complements and on the degree of product differentiation. We also find that licensing always increases social welfare, although it may hurt consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 33 publications
0
13
3
Order By: Relevance
“…He showed that the two forms of two-part tariffs are equivalent to each other regarding both the profitability and the welfare implications. Other works on a two-part ad valorem royalty mechanism include Heywood et al (2014), Colombo and Filippini (2015), and San Martín and Saracho (2015). While these papers assume constant returns to scale, Colombo and Filippini (2016) compared several licensing mechanisms -ad valorem royalty, per-unit royalty and revenue-royalty -under the assumption of decreasing returns to scale in a Cournot duopoly.…”
mentioning
confidence: 99%
“…He showed that the two forms of two-part tariffs are equivalent to each other regarding both the profitability and the welfare implications. Other works on a two-part ad valorem royalty mechanism include Heywood et al (2014), Colombo and Filippini (2015), and San Martín and Saracho (2015). While these papers assume constant returns to scale, Colombo and Filippini (2016) compared several licensing mechanisms -ad valorem royalty, per-unit royalty and revenue-royalty -under the assumption of decreasing returns to scale in a Cournot duopoly.…”
mentioning
confidence: 99%
“…(), Bagchi and Mukherjee (), Kitagawa et al . (), and San Martin and Saracho (). On the other hand, we also discuss results under the Levitan–Shubik demand system for the robustness check in the Discussion and Conclusion section.…”
mentioning
confidence: 99%
“…San Martín and Saracho () extend the analysis to differentiated products. Boccard () shows that the result by San Martín and Saracho () holds also in the case of an outsider patentee, even in the absence of demand uncertainty, provided that there is no a unique potential licensee.…”
mentioning
confidence: 99%
“…The equilibrium third‐stage quantities are those derived in San Martín and Saracho (), under a linear demand function of this type: P i = a − q i − θq − i .…”
mentioning
confidence: 99%